2008
DOI: 10.1253/circj.cj-07-0921
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-Associated Virus-Mediated Gene Transfer in a Rabbit Vein Graft Model

Abstract: therosclerosis causing vascular disease remains one of the most important predictors for morbidity and mortality, being usually treated via angioplasty and bypass grafting. In coronary artery surgery, autologous saphenous vein and internal thoracic artery grafts are the most widely used bypass conduits. 1 Late graft failure after the operation, caused by stenoses and occlusion of the venous grafts as a result of intima hyperplasia or progression of the vascular disease, leads to a high incidence of re-operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The 24 weeks of veingraft transgene expression reported here is several months longer than we could find in any previous study, including those using adeno-associated virus (AAV) and lentivirus. 42,43 Both AAV and lentivirus are potentially useful vectors for preventing vein-graft disease. AAV has the advantage of low immunogenicity and an excellent safety record in humans; lentivirus could possibly provide longer term expression due to its ability to integrate in the genome.…”
Section: Durable Transgene Expression In Vein Graftsmentioning
confidence: 99%
“…The 24 weeks of veingraft transgene expression reported here is several months longer than we could find in any previous study, including those using adeno-associated virus (AAV) and lentivirus. 42,43 Both AAV and lentivirus are potentially useful vectors for preventing vein-graft disease. AAV has the advantage of low immunogenicity and an excellent safety record in humans; lentivirus could possibly provide longer term expression due to its ability to integrate in the genome.…”
Section: Durable Transgene Expression In Vein Graftsmentioning
confidence: 99%
“…The transfected gene is not able to insert itself into the host genome and is thus diluted with cell proliferation. Adeno-associated virus has also been reported as a useful delivery vector, with reduced immunogenicity [117]. Lentivirus vector, which is a member of the retrovirus vector family, has advantages over adenovirus vectors.…”
Section: Novel Targets For Management Of Vein Graft Thickening: Spotlmentioning
confidence: 99%
“…In the past, Kilian et al [15] showed transfected native rabbit jugular veins with recombinant AAV vector,Moreover, low immunogenicity of AAV may also allow long-term transgene expression; Sen et al [16] showed that AAV1 have advantages over AAV2 for vascular gene delivery at low titres; Stachler et al [17] showed that mosaic AAV1 particles in a 50-100-fold enhancement in endothelial cell gene transfer and suggest that mosaic virions hold significant promise for targeted gene delivery to the vasculature.In the present study we showed that recombinant mosaic AAV2/1 facilitates an effective gene transfection in an autologous rabbit vein grafts model. Our data have shown that AAV2/1.CGRP was transfected effectively to vein grafts( Fig.…”
Section: Discussionmentioning
confidence: 99%